Supporting Holistic Wellbeing for Performing Artists During the COVID-19 Pandemic and Recovery: Study Protocol - Stuckey, Melanie; Richard, Véronique; Decker, Adam; Aubertin, Patrice; Kriellaars, Dean (Frontiers in Psychology, 2021)
The COVID-19 pandemic resulted in the abrupt closure of circus schools, venues, and companies, introducing a myriad of novel stressors. Performers and students must now attempt to maintain their technical, physical, artistic, creative, and cognitive abilities without in-person support from their coaches and must manage the isolation from their training and performing spaces. For circus artists, the transposition of the work space to a home environment is not possible, which creates novel stressors that could lead to the exacerbation and escalation of mental health issues. The purpose of this study is to develop, implement and evaluate a holistic interventional program based on the socio-ecological model of resilience and operationalized through physical literacy. This will be a prospective longitudinal study with a retrospective comparison to data from a similar student cohort pre-pandemic. Interventions were designed using a population-specific, participant-based developmental model within a knowledge translation framework. The interventional program includes group webinars, small group information sessions, and one-on-one Zoom meetings, in addition to the distribution of electronic educational materials. The interventions will holistically provide psychological, physical, social, technical, artistic, and creative supports. Resources will be deployed throughout the closure period and through recovery, as transitions to return to training after prolonged hiatus will magnify known psychological and physical difficulties. Repeated, longitudinal assessment of students will be utilized to track changes over time at key transitions in the pandemic and school year and will be compared to a pre-pandemic school year. The framework for this program will be translatable to other performing arts and high-performance contexts. The program has implications for the mental health and overall wellbeing of artists and for cultural and economic recovery of the industry.